(untitled) (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2025)
This article suggests a “counterfactual” reading of the works of Juan José Saer (1937-2005), inspired by the analysis of the works of Jorge Luís Borges (1899-1986) and Julio Cortázar (1914-1984) conducted by Vraneš (2024). Given that the year 2025 has been declared in Argentina as the year of Saer, this article has a twofold goal: paying tribute to Juan José Saer and sketching an answer to the following question: How would Saer regard the current practice of using artificial intelligence (AI) to generate literary texts?